Preliminary study of the production of metabolites from in vitro cultures of C. ensiformis (2020)
Background: Canavalia ensiformis is a legume native to Central and South America that has historically been a source of protein. Its main proteins, urease, and lectin have been extensively studied and are examples of bioactive compounds. In this work, the effect of pH and light effects on the growth of C. ensiformis were analyzed. Also, the bioactive compounds such as phenols, carotenoids, chlorophyll a/b, and the growth of callus biomass of C. ensiformis from the effect of different types of light treatments (red, blue and mixture) were evaluated. Likewise, the antioxidative activity of C. ensiformis extracts were studied and related to the production of bioactive compounds. For this, a culture of calluses obtained from seeds were carried out. For the light experiments, polypropylene boxes with red, blue, combination (1/3, 3/1 and 1/1 R-B, respectively) lights and white LED were used as control. In each treatment, three glass containers with 25 ml of MS salts containing 0.25 g of fresh callus were seeded. Results: The results have shown that the pH of the culture medium notably affects the increase in callogenic biomass. It shows that the pH of 5.5 shows better results in the callogenic growth of C. ensiformis with an average increase of 1.3051 g (198.04%), regarding the initial weight. It was found that the pH 5.5 and the 1/3 R-B LED combination had higher production of bioactive compounds and better antioxidant activity. At the same time, the red-light treatment was least effective. Conclusions: It was possible to find the ideal conditions of important growth under conditions of pH and light of C. ensiformis. Likewise, it is evaluated whether the production of compounds of interest, such as phenolic compounds and carotenoids, occurs under these conditions. The highest production of calluses occurs in the 1/3 R-B LED combined light treatment, which showed a significant increase in biomass, followed by B. From this study, it could be demonstrated that C. ensiformis produces compounds such as phenols and carotenoids in vitro culture that are essential for the antioxidant activity of the plant. © 2020 The Author(s).